Higher Education Web Information System Usage Analysis with a Data Webhouse - Carla Teixeira Lopes (2006)
Usage analysis of a Web Information System is a valuable help to predict user needs, to assess systems impact and to guide to its improvement. This is usually done analysing clickstreams, a low-level approach, with huge amounts of data that calls for data warehouse techniques. This paper presents a dimensional model to monitor user behaviour in Higher Education Web Information Systems and an architecture for the extraction, transformation and load process. These have been applied in the development of a data warehouse to monitor the use of SIGARRA, the University of Portos Higher Education Web Information System. The efficiency and effectiveness of this monitorization method were confirmed by the knowledge extracted from a 3 month period analysis. A brief description of the main results and recommendations are also described.